The short story in South Africa
1 online resource
Keywords: "This book considers the key critical interventions on short story writing in South Africa written in English since the year 2000. The short story genre, whilst often marginalized in national literary canons, has been central to the trajectory of literary history in South Africa. In recent years, the short story has undergone a significant renaissance, with new collections and young writers making a significant impact on the contemporary literary scene, and subgenres such as speculative fiction, erotic fiction, flash fiction and queer fiction expanding rapidly in popularity. This book examines the role of the short story genre in reflecting or championing new developments in South African writing and the ways in which traditional boundaries and definitions of the short story in South Africa have been reimagined in the present. Drawing together a range of critical interventions, including scholarly articles, interviews and personal reflective pieces, the volume traces some of the aesthetic and thematic continuities and discontinuities in the genre and sheds new light on questions of literary form. Finally, the book considers the place of the short story in twenty-first century writing and interrogates the ways in which the short story form may contribute to or recast ideas of the post-apartheid or post-transitional. The perfect guide to contemporary short story writing in South Africa, this book will be essential reading for researchers of African literature"--